Students Reading Achievement Based on Their Intelligence Quotient (IQ): A Case Study - Rahmah, Aufa; Kardena, Absharini; Irwandi, Irwandi; Amiza, Elsi (Pusdikra-Publishing.com, 2024)
This research was conducted to determine the factors that caused some students to have high IQ but low English reading achievement and vice versa. The research aimed to find out what factors caused students to have high intellectual intelligence but low reading achievement and vice versa. This type of research was a qualitative method with a case study research design. Participants in this research were grade VIII students at SMPN 4 Bukittinggi, and using purposive sampling techniques, the researchers selected 9 participants for this research. The instruments used in this research were interviews and observations checklist of students. The results of the analysis showed that there were two factors that caused students to have high IQ but low English reading achievement and vice versa. This could be seen from the results of interviews and observation checklists with students, namely internal factors are physiological, intelligence, talents, interests, student activity during the learning process, and also external factors, namely the role of parents, teachers, learning media, infrastructure, curriculum, school time, and mass media. It can be concluded that the factors causing students to have high IQ but low achievement in learning English and vice versa were internal and external factors, and were also supported by aspects of student activity in the English learning process.